Effects of low level laser therapy on the cicatricial dehiscence in the postoperative period of lipoabdominoplasty. Case Report - Roque, Vanessa Siqueira; Silva, Rodrigo Marcel Valentim da; Sousa, Maria Karolina Ferreira de; Silva, Julio Davi Costa e; Carreiro, Eneida de Morais; Meyer, Patrícia Froes (Manual Therapy, Posturology & Rehabilitation Journal, 2017)
Introduction: The surgical procedure is used for the treatment of external and internal injuries and diseases, performed through operations. In this context, the plastic surgery has the purpose of artificially reconstructing a part of the body. Among the various types of surgical interventions, lipoabdominoplasty is more accomplished, correcting the aesthetic and functional deformities of the abdomen, adding a better and more harmonious abdominal contour. Objective: To analyze the effect of the application of the low power laser in the repair of the cicatricial dehiscence in the postoperative period of lipoabdominoplasty in one patient. Methodology: A 25-year-old female patient who underwent lipoabdominoplasty surgery sought physical therapy in March 2017. She had cicatricial dehiscence, and started the pharmacological and physiotherapeutic treatment with low-power laser, AsGa, 12 s, 6J, non-contact. Results: It was observed improvement of the dehiscence progressively, with reduction of the local inflammation, reorganization of the tissue and closure of the wound, presenting in the end only the surgical scar. Conclusion: This study demonstrated positive effect of laser therapy, recovering the injured tissue, signaling a new non-invasive approach to a safe and beneficial treatment.